2014
DOI: 10.1007/s10508-014-0346-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Vulnerability and HIV-Related Sexual Risk Among Men who have Sex with Men and Women in the United States

Abstract: In the U.S., HIV is concentrated among men who have sex with men (MSM), some of whom have had female partners (MSMW). MSMW are disproportionately impacted by psychosocial vulnerabilities, like depression and substance use that increase sexually transmitted infection (STI) and HIV risk. Research on psychosocial vulnerability and HIV-related sexual risk among MSMW is warranted to reduce infection transmission among MSM and to prevent bridging to female partners. We analyzed data from Wave IV (2007)(2008) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 68 publications
4
29
0
Order By: Relevance
“…Thus, in the final model, more experiences of sexual violence in the past 12 months were independently associated with not living with a spouse or steady partner, having a history of childhood sexual abuse, more adult experiences of homophobia, and higher scores on depression and hostility symptoms (see Table 2). Since previous research has shown differences between MSM and men who have sex with men and women (MSMW) in terms of sexual violence and other psychosocial factors (Davis et al, 2015; Dyer, Regan, Pacek, Acheampong, & Khan, 2015; Wang et al, 2015), we re-ran the hierarchical regression model excluding 48 participants who reported sex with women in the past two months. The substantive findings were mostly unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the final model, more experiences of sexual violence in the past 12 months were independently associated with not living with a spouse or steady partner, having a history of childhood sexual abuse, more adult experiences of homophobia, and higher scores on depression and hostility symptoms (see Table 2). Since previous research has shown differences between MSM and men who have sex with men and women (MSMW) in terms of sexual violence and other psychosocial factors (Davis et al, 2015; Dyer, Regan, Pacek, Acheampong, & Khan, 2015; Wang et al, 2015), we re-ran the hierarchical regression model excluding 48 participants who reported sex with women in the past two months. The substantive findings were mostly unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with other research, our study found that fewer BMSMW were HIV infected compared to BMSMO. 17,28,29 This could reflect the comparatively lowered risks for HIV transmission per sexual event as BMSMW have sex with some high-risk men and low-risk heterosexual women, while BMSMO engage in sex with other men, exclusively. 40 Specifically, female partners for BMSMW have lower HIV prevalence than that of male partners, which may explain the comparatively lower HIV prevalence for this group.…”
Section: Discussionmentioning
confidence: 99%
“…9 While BMSMW have lower HIV prevalence compared to BMSMO, they often report elevated levels of compound, interconnected factors (e.g., internalized homophobia, cocaine use) that correspond with increased risk and frequency of potential exposure to HIV, which places their male and female partners at increased risk, as well. 17,28,29 To best understand how to reduce disproportionate infection among BMSMW and to prevent transmission from these men to their male and female partners, research is needed to compare BMSMO and BMSMW on substance use, psychosocial factors, and behaviors that correspond with HIV risk. Therefore, there is a need to utilize existing data to develop an understanding of risk in order to tailor interventions for BMSMW.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial factors can play a crucial role in determining MSMW vulnerability, particularly in terms of risk behaviour, and for these reasons this sub-population can be identified as a priority population for targeted HIV and STI prevention interventions (9) (10).…”
Section: Introductionmentioning
confidence: 99%